Penerapan Algoritma Boyer Moore Untuk Pencarian Kata Antonim-Sinonim Pada Kamus Berbasis Android - Fahrul Roji, Fahrul Roji (Jurnal Publikasi Teknik Informatika, 2025)
The development of information technology drives the need for quick access to language resources, including the search for antonyms and synonyms in digital dictionaries, especially for students and the general public. However, conventional applications' limited internet access and slow search processes pose significant obstacles. This research aims to develop an Android-based antonym-synonym dictionary application by applying the Boyer-Moore algorithm to improve the efficiency of lexical data searching. The research uses a software engineering approach with the Rapid Application Development (RAD) method, involving observation, literature study, and system implementation testing. Data is analyzed based on search performance using string-matching simulations. The research results indicate that the Boyer-Moore algorithm can significantly accelerate the search process compared to conventional methods, with accurate and relevant results to user keywords. The conclusion of this research shows that implementing appropriate string-matching algorithms can improve the quality of word search systems in digital dictionary applications, providing practical contributions to educational software development and supporting more inclusive and efficient language literacy in the context of mobile technology.